The use of physical indicators for discussing the urbanization costs of horizontal housing estates - Inouye, Kelly Paiva (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
This paper proposes a set of measures for evaluating different urban arrangements in terms of cost. The selection of the measures was based on municipal, state and federal legislation, concerned with land urbanization, as well as on the literature concerned with definitions and criteria for the conception of housing estates. It was also based on the study of five horizontal housing projects developed by the Housing and Urban Development Company (CDHU) from the State of São Paulo, and one carried out by a private developer. The paper initially presents a brief discussion of low-income housing in Brazil and introduces some key concepts related to the topic. Then, the urbanization costs involved in the development of a housing estate and the proposed measures are discussed. Finally, a comparative analysis of two case studies is carried out, aiming to illustrate how such measures can support decision making in the conception of low-income housing estates.